Rise CKMB and Myoglobin Levels in Non-Cardiac Patients of Ischemic Stroke Presenting to Emergency Department of a Tertiary Care Hospital - Muhammad Dawood; Yasir Abbas; Asif Hashmat; Andaleeb Khan; Kamil Rehman Butt; Shahana Rehman (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the rise in CKMB and Myoglobin levels and associated factors in non-cardiac patients of ischemic stroke presenting to the Emergency Department of a Tertiary Care Hospital.